Energy Efficient Coded Random Access for the Wireless Uplink - Kowshik, Suhas S.; Andreev, Kirill; Frolov, Alexey; Polyanskiy, Yury (IEEE transactions on communications, 2020)
We discuss the problem of designing channel access architectures for enabling fast, low-latency, grant-free, and uncoordinated uplink for densely packed wireless nodes. Specifically, we study random-access codes, previously introduced for the AWGN MAC, in the practically more relevant case of Rayleigh fading, when channel gains are unknown to the decoder. We propose a random coding achievability bound, which we analyze both non-asymptotically and asymptotically. As a candidate practical solution, we propose an explicit iterative coding scheme. The performance of such a solution is surprisingly close to the finite blocklength bounds. Our main findings are twofold. First, just like in the AWGN MAC, we see that jointly decoding a large number of users leads to a surprising phase transition effect, where, at spectral efficiencies below a critical threshold, a perfect multi-user interference cancellation is possible. Second, while the presence of Rayleigh fading significantly increases the minimal required energy-per-bit, the inherent randomization introduced by the channel makes it much easier to attain the optimal performance via iterative schemes. We hope that a principled definition of the random-access model, together with their information-theoretic analysis, will open the road towards unified benchmarking and performance comparison of various random-access solutions for the 5G/6G.